ANALISIS KEPUASAN IBU BERSALIN DI RUANG KEBIDANAN - Hesti Kurniasih; Vina Nurul Utami; Sumiyati Sumiyati; Affi Zakiyya (Jurnal Sains Kebidanan, 2020)
Patient satisfaction is the most important thing that needs to be prioritizied by the Hospital. To achieve the quality of service according to patient expectations, the hospital always prioritizes patient satisfaction through continous improvement in the quality of service by implementing correct practives, increasing human resource competence (HR) and applying adequate technology. Research this is a type of quantitative research with approach cross sectional. The population in this, study were all maternity patients for a period of 1 month. The number of samples that met the inclusion criteria from September 11 to October 11, 2017 wa 77 people. Univariate analysis with the Importnace-method Performance Analysis. The IPA method is done by calculating the level of conformity and a Cartesian diagram of expectations and reality. To determine the different test, the researcher first conducted a normality test on variabels; tangible; reliability, responsivess, assurance, and empathy using Kolmogorof-Smirnof (because the sample 50) with a significant value0.05 (Dahlan, 2014). It was concluded that the data was not normally distrtributed. So researchers use the Wilcoxon test (because the data are not normally distributed) to determine the different test (Dahlan, 2014). On the dimensions of the study carried out still requires changes to improve patient satisfaction.